Comparative Effectiveness of Whole-Body Narrowband Ultraviolet B (NB-UVB) 311 nm, Targeted NB-UVB 311 nm, and Excimer Lamp 308 nm in Pediatric Vitiligo: A Retrospective Single-Center Study - Nikko Vanda Limantara; Amelia Pungky; Rizky Rahma Wijayanti; Retno Danarti; Flandiana Yogianti; Arief Budiyanto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Vitiligo is an autoimmune skin disorder marked by depigmented macules or patches. Pediatric vitiligo is common, accounting for approximately one-quarter to one-half of all cases. Phototherapy modalities such as narrowband ultraviolet B (NB-UVB) 311 nm and excimer 308 nm are widely used to treat vitiligo in children. However, comparative data in Indonesian children remain scarce. Purpose: To compare the effectiveness of whole body (WB) NB-UVB 311 nm, targeted NB-UVB 311 nm, and excimer lamp 308 nm in pediatric vitiligo patients. Methods: This retrospective study included children (<18 years old) with vitiligo treated with phototherapy at the Department of Dermatology and Venereology, Gadjah Mada Univeristy/ Dr. Sardjito Hospital, Yogyakarta, from January 2022 to May 2025. Patients received WB NB-UVB (311 nm), targeted NB-UVB (311 nm), or excimer lamp (308 nm) therapy. Vitiligo Area Severity Index (VASI) scores were assessed at baseline, after 36 and 72 phototherapy sessions. Changes were analyzed using the Friedman test and Kruskal-Wallis/Mann-Whitney U tests. Result: Among 44 patients (median age 10 years; 50% female), most received targeted NB-UVB 311 nm (40.9%), followed by excimer 308 nm34.1%) and WB NB-UVB 311 nm (25.6%). All groups showed significant improvement over time (p<0.05). At 72 sessions, target VASI improvement was highest in the excimer group 308 nm (75.00%), followed by targeted NB-UVB 311 nm (70.77%), and WB NB-UVB 311 nm (45.78%), with no significant differences between groups (p=0.931). Conclusion: All three modalities were effective. Excimer 308 nm and targeted NB-UVB 311 nm yielded comparable outcomes in localized vitiligo.